Accessibility, Inclusivity, and Satisfaction Persons with Disabilities in University Libraries of Pakistan - Rabia Mumtaz; Dr. Mahe-Bushra Asghar (IJoLIS, 2025)
Purpose: The study aimed to assess the satisfaction levels of Persons with Disabilities (PWDs) regarding library resources and services offered in university libraries of Punjab, Pakistan and to identify the obstacles encountered by PWDs in accessing these resources and services within the university libraries of Punjab, Pakistan. Methodology/approach/design: This study used a quantitative approach based on a survey research methodology. The population consisted of university libraries of Punjab province that had separate centers for persons with disabilities. Data was obtained from persons with disabilities via a questionnaire. Using the SPSS software, descriptive and inferential statistical tests were performed. These tests included one-way ANOVA, measures of central tendency and dispersion, as well as frequency and percentage calculations. Findings: The results of the study highlighted various challenges encountered by PWDs in accessing required resources to meet their needs within the library environment. Among the top-rated problems identified by respondents are physical obstacles, restricted access to content in accessible formats, and inadequate signage and information for PWDs The satisfaction levels of persons with disabilities about library resources and services offer substantial information into their experiences and perceptions within the library context. Among the top-rated aspects of satisfaction are the availability of comfortable spaces for reading and studying, accessibility of staff assistance, and satisfaction with library programs and events. Conclusion: The study revealed several key elements that contribute to the positive library experience of PWDs. These elements include the availability of quiet areas for reading and studying, the friendliness of library personnel, and the quality of library programs and events. The undertaken research reveals that PWDs generally report a high degree of satisfaction over the availability of accessible resources, which include braille books, large-print texts, audiobooks, and digital materials compatible with screen readers. Originality: The research highlights the need for libraries to implement comprehensive strategies that address these obstacles and ensure that PWDs have equal access to library resources and services.